Maritime Regimental System: Fostering Discipline and Professional Success - John Rhome E. J. Mamangon (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This paper analyzes how the maritime regimental system instills discipline among maritime cadets and graduates and aids in their professional development. We focus primarily on graduates from the Philippine Merchant Marine Academy (PMMA) and the Maritime Academy of Asia and the Pacific (MAAP) and the challenges faced. Participants in this study include 106 graduates and 192 First-Class cadets and cadettes. Participants for the qualitative study included six shipping company officers that oversee cadets, and six school administrators that implement the Maritime Regimental System. The study employs a mixed methods, convergent parallel design, and data collection was achieved via the internet. According to the results, professional success and the regimental system are influenced most substantially by leadership. Training was said to bolster confidence among cadets and bolstered the ability to oversee and evaluate decision making on training ships. Graduates confirmed that the system aids in adjusting to training on a ship, adherence to safety regulations, and aids in progression to assume roles of authority. The system's overall impact on character, work ethic, and professional training was found to be positive.Several challenges related to the regimental system were identified. These included limited facilities, costs that constrain creativity, and a ratio of staff to students that hinders the possibility of close-up and individualized mentoring. From these, conclusions were drawn, and suggestions included areas for potential future non-regimental and regimental school-based research. Overall, the maritime regimental system is effective in instilling discipline and preparing cadets for success in their careers.